The Association Between Age and Prognosis in Patients Under 45 Years of Age With Anti-NMDA Receptor Encephalitis - Sun, Yueqian; Ren, Guoping; Ren, Jiechuan; Shan, Wei; Han, Xiong; Lian, Yajun; Wang, Tiancheng; Wang, Qun (Frontiers in Neurology, 2020)
This study aims to evaluate the association between age and prognosis in patients with anti-N-methyl-D-aspartate receptor encephalitis (anti-NMDARE) under the age of 45 years. A retrospective study was conducted in patients younger than 45 years diagnosed as anti-NMDARE in four hospitals in China. Age at admission was divided into four categories: <15, 15-24, 25-34, 35-45 years. Neurological prognosis was evaluated using modiﬁed Rankin Scale. Adjusted multivariable logistic regression was used to analyze the association. The multivariable-adjusted odds ratios (95% confidence interval) of prognosis in anti-NMDARE across the categories of age were as follows: in males, 1.00 (reference), 4.76 (0.39 - 58.76), 13.50 (0.79 - 230.40), and 8.81 (0.36 - 218.39) (P for trend = 0.171); in females, 1.00 (reference), 7.27 (0.36 - 146.19), 20.08 (1.09 - 370.39), and 54.41 (1.60 - 1849.10) (P for trend = 0.01). We concluded that the increasing age was associated with a poorer prognosis of anti-NMDARE in females but not males.